Pengaruh Menejemen Waktu Terhadap Kemandirian Belajar Mahasiswa - Syafaruddin; Handoko (Arus Jurnal Pendidikan, 2025)
This study aims to investigate the influence of time management on students' learning independence. A quantitative approach with a correlational method was employed in this research. The sample consisted of 68 second-semester students from the mathematics education program at a state university in Lampung, Indonesia. Data were analyzed using SPSS software. The findings revealed a significance value (Sig.) of 0.000, which is lower than the threshold of α = 0.05, and a coefficient of determination (R²) of 0.740. These results indicate that time management contributes 74.0% to students' learning independence, while the remaining 26.0% is influenced by other factors beyond the scope of this study. Furthermore, a positive regression coefficient of 1.067 suggests that an improvement in time management is directly associated with an increase in learning independence. In conclusion, time management has a significant and positive impact on students' learning autonomy. The better students manage their time, the more independent they become in their learning processes.